Peran Kebijakan dalam Peningkatan Performa Layanan BRT Transjakarta - Mutiasari Kurnia Devi; Rinawanti Safitri; Fahril Fanani (SPECTA Journal of Technology, 2021)
Public transportation service improvement in urban area, such as Bus Rapid Transit (BRT), becomes the main issue among transport planners nowadays. BRT has been a popular transit system which provide an easy dan fast service for satisfying the transport needs, particularly in developing countries. This transport mode offers high quality mass transit system yet still in affordable cost, which is necessary for developing countries. Jakarta becomes the first Southeast Asia country who applied the BRT system. This study aims to gain insights towards the role of policies in facilitating the improvement of TransJakarta performance and reach 1 million passengers in early 2020. Understanding the policy aspect, both central and regional policies which can improve the public transport performance, will possibly provide a broader perspective among policymakers who developing and implementing the BRT systems, particularly in developing countries. For this purpose, conceptual framework was employed to explain how policy implementation could improve the BRT performance, which collected through secondary data, mostly various planning documents and TransJakarta operational reports. By using the qualitative approach, results show that various policies could facilitate the improvement of TransJakarta performances. The improvements occurred in line with the institutional reforms and the development of BRT system, such as routes, capacities, and integration with other mass transit systems.